Taxonomic status of Macaronesian Eucyclops agiloides azorensis (Arthropoda: Crustacea: Copepoda) revisited – morphology suggests a Palearctic origin - Hołyńska, Maria; Sługocki, Łukasz; Ghaouaci, Souad; Amarouayache, Mounia (European Journal of Taxonomy, 2021)
Macaronesia, with the exception of the Azores, is one of the few Palearctic provinces where basic taxonomic information on the freshwater copepods is still lacking. We redescribed Eucyclops azorensis, a cyclopid crustacean so far known only in the Azores, and report the occurrence of this species in Algeria and Madeira Island. Eucyclops azorensis was formerly considered to be a subspecies of E. agiloides (East Africa); therefore, the latter species is redescribed here as well based on type and non-type material. Morphological comparisons between E. azorensis, E. agiloides and other taxa (E. serrulatus and E. roseus), assumed to be closely related to our target species, support a closer relationship between E. azorensis and E. serrulatus (Palearctic) than between E. azorensis and E. agiloides (Afrotropical). The slight differences between E. azorensis and E. serrulatus in the surface ornamentation of the antennal coxobasis and intercoxal sclerites of legs 1 and 4 suggest a relatively young separation of these lineages. Eucyclops agiloides is morphologically close to E. roseus (temperate and subtropical Asia, southeastern Europe, East Africa). The numerous and clear-cut differences indicate a species rather than subspecies-level differentiation between E. agiloides and E. roseus, unlike what was formerly proposed in the taxonomic literature.